Bloody rose - Eames, Nicholas (Eames, Nicholas. Band, 2018)
"A standalone adventure featuring a band of female mercenaries in the world of Kings of the Wyld from author Nicholas Eames, who has been hailed as "the voice of modern fantasy" by Michael R. Fletcher. Live fast, die young. Tam Hashford has always dreamed of living through glory days of her own. With a renowned mercenary for a mother and an illustrious bard for a father, battles and adventure seem the only way to really live. So when she learns that the most revered mercenary crew in Grandual is in need of a bard, she grabs her lute and goes on tour. Led by the infamous Bloody Rose, Tam and her new band embark on a mission that will earn them everlasting fame -- or certain death"--